Purification and characterization of a harsh conditions-resistant protease from a new strain of Staphylococcus saprophyticus - Uttatree, Sasithorn; Charoenpanich, Jittima (Agriculture and Natural Resources, 2018)
A major road block to the industrial usage of known proteases is their limited stability under harsh conditions. Hence, there is always a need for newer enzymes with novel properties that can further satisfy all industrial demands. This study described a benthic marine bacterium, Staphylococcus saprophyticus that secretes an alkaliphilic and broad-temperature active protease (10-80°C). The protease was successfully purified 42.66-fold using 70-80% ammonium sulfate precipitation and gel-permeable column chromatography. It had a relative molecular mass of 28 kDa on sodium dodecyl sulphatepolyacrylamide gel electrophoresis and retained high activity and significant stability at 60-80°C, over a wide range of pH (3.0-12.0), inhibitors and metal ions. Furthermore, the enzyme was stable in surfactants (such as sodium dodecyl sulfate), oxidizing agents (such as H2O2), bleaching agents (such as zeolite) and hydrophobic solvents (such as benzene, hexanes and hexadecane). These properties support the enzyme's potential as a vigorous biocatalyst for industrial applications.